1996
DOI: 10.1093/ndt/11.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bcl-2 oncoprotein in various types of glomerulonephritis and renal allografts

Abstract: The absence of bcl-2 expression in normal and diseased glomeruli suggests and supports the reported notion that the mechanism of apoptosis may be available in the injured glomerulus. Moreover, bcl-2 expression in podocytes near intraglomerular fibrotic lesions and in epithelial cells of early adhesions and cellular crescents indicates the deregulation of apoptosis and its possible role in the progression of glomerular scarring. Key words: apoptosis; bcl-2 oncoprotein; glomerulonephritis; immunohistochemical; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…6 ). The pattern of Bcl-2 expression in normal and diseased glomeruli suggests and supports the reported notion that the mechanism of apoptosis may be increased in the injured glomerulus [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…6 ). The pattern of Bcl-2 expression in normal and diseased glomeruli suggests and supports the reported notion that the mechanism of apoptosis may be increased in the injured glomerulus [ 46 ].…”
Section: Discussionsupporting
confidence: 83%
“…[21] Changes of bcl-2 and bax expression have been described in various experimental models [22,23] and human glomerulonephritis. [12,16] In this study, a significantly higher bcl-2 and bax expression was identified in the renal tissue of patients with GN compared to the controls. Bcl-2 and bax proteins were mainly localized within tubular epithelial cells, in the renal interstitium and to a lesser extent in the glomeruli.…”
Section: Discussionsupporting
confidence: 50%
“…In the case of bcl‐2 expression, bcl‐2 transcripts were well represented in the majority of normal kidney samples but were extremely low or undetectable in several RCC. The expression of bcl‐2 has previously been examined in normal kidney and RCC by immunohistochemical analysis; 34 , 35 , 48 , 49 bcl‐2 was found to be consistently expressed in normal kidney localized mainly to the renal distal tubular and glomerular parietal epithelial cells 34 , 35 , 48 , 49 . However, a more variable expression of bcl‐2 was observed in RCC, 34 , 35 and appeared to relate to the tumour type in that tubulopapillary carcinomas strongly expressed bcl‐2 whereas only a few, or no bcl‐2‐positive cells, were observed in clear cell carcinomas 34 .…”
Section: Discussionmentioning
confidence: 99%